La protección de datos personales en los estados que conforman la Comunidad Andina: estudio comparado y precisiones para un modelo interamericano de integración (Tema Central) - Ordóñez Pineda, Luis (2017)
During the 20th century and especially in the last decades there has been an important recognition of the personal data protection as a fundamental right, both in the International Treaties and Agreements and in the Constitutions of different countries. This has resulted in a legislative development of fundamental rights in order to regulate the treatment of personal information both in public and private sector. In Ecuador, the emergence of the right to informational self-determination is framed within the principles preserved in the Andean Neo Constitutionalism stated in participatory democracy and in the Constitutionalism of new fundamental rights, fundamentally. This research is aimed at studying –in the context of the Andean Community– the constitutional, jurisprudential and doctrinal precedents that frame the origin and development of this fundamental right. Based on the European experience, this analysis aims to initiate an Interamerican Model of Integration for a balanced regulation respect to the processing of the personal data.